Nitrogen dioxide exposures from biomass cookstoves in the Peruvian Andes. (6th March 2020) - Kephart, Josiah L.; Fandiño‐Del‐Rio, Magdalena; Williams, Kendra N.; Malpartida, Gary; Steenland, Kyle; Naeher, Luke P.; Gonzales, Gustavo F.; Chiang, Marilú; Checkley, William; Koehler, Kirsten; ,
Abstract: Background: Household air pollution from biomass cookstoves is a major contributor to global morbidity and mortality, yet little is known about exposures to nitrogen dioxide (NO2 ). Objective: To characterize NO2 kitchen area concentrations and personal exposures among women with biomass cookstoves in the Peruvian Andes. Methods: We measured kitchen area NO2 concentrations at high‐temporal resolution in 100 homes in the Peruvian Andes. We assessed personal exposure to NO2 in a subsample of 22 women using passive samplers. Results: Among 97 participants, the geometric mean (GM) highest hourly average NO2 concentration was 723 ppb (geometric standard deviation (GSD) 2.6) and the GM 24‐hour average concentration was 96 ppb (GSD 2.6), 4.4 and 2.9 times greater than WHO indoor hourly (163 ppb) and annual (33 ppb) guidelines, respectively. Compared to the direct‐reading instruments, we found similar kitchen area concentrations with 48‐hour passive sampler measurements (GM 108 ppb, GSD 3.8). Twenty‐seven percent of women had 48‐hour mean personal exposures above WHO annual guidelines (GM 18 ppb, GSD 2.3). In univariate analyses, we found that roof, wall, and floor type, as well as higher SES, was associated with lower 24‐hour kitchen area NO2 concentrations. Practical Implications: Kitchen area concentrations and personal exposures to NO2 from biomass cookstoves in the Peruvian Andes far exceed WHO guidelines. More research is warranted to understand the role of this understudied household air pollutant on morbidity and mortality and to inform cleaner‐cooking interventions for public health.